2020
DOI: 10.4097/kja.d.18.00269
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided bilateral quadratus lumborum block vs. intrathecal morphine for postoperative analgesia after cesarean section: a randomized controlled trial

Abstract: Background: Adequate pain control after cesarean section (CS) is crucial for mothers caring for newborns, and early ambulation to avoid thromboembolism and chronic abdominal and pelvic pain. This randomized controlled trial compared the efficacy of quadratus lumborum block (QLB) and intrathecal morphine (ITM) for analgesia after CS. Methods: Ninety women at ≥ 37 weeks pregnancy scheduled for elective CS were enrolled. All patients received spinal anesthesia and post-operative QLB. They were randomly allocated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
6
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(79 citation statements)
references
References 27 publications
(42 reference statements)
1
70
6
1
Order By: Relevance
“…Compared with IT morphine alone, posterior QLB alone had a signi cantly shorter pain-free period, and patients required signi cantly more morphine during the rst 24 hours. This result is in contrast to the ndings of Salama ER, et al 16 who found the time to rst morphine dose to be signi cantly longer with QLB than IT morphine. Salama ER, et al reported a median (min, max) time of 8 h (3-24) in IT morphine vs. 17 in QLB, whereas we observed the median pain free period to be 2.50 h (95% CI: 1.04-3.96) in…”
Section: Discussioncontrasting
confidence: 99%
“…Compared with IT morphine alone, posterior QLB alone had a signi cantly shorter pain-free period, and patients required signi cantly more morphine during the rst 24 hours. This result is in contrast to the ndings of Salama ER, et al 16 who found the time to rst morphine dose to be signi cantly longer with QLB than IT morphine. Salama ER, et al reported a median (min, max) time of 8 h (3-24) in IT morphine vs. 17 in QLB, whereas we observed the median pain free period to be 2.50 h (95% CI: 1.04-3.96) in…”
Section: Discussioncontrasting
confidence: 99%
“…Of these, four were excluded because of nonrandomization 43 and incorrect comparison. 3,29,44 Thus, 12 full-text, randomized, controlled trials [4][5][6][7][8][38][39][40][41][42]45,46 were included in this systematic review and meta-analysis. Supplemental Digital Content 3 (http://links.…”
Section: Resultsmentioning
confidence: 99%
“…• Quadratus lumborum block does not provide analgesic benefit when compared with or in addition to spinal morphine for postcesarean analgesia • In patients who do not receive spinal morphine, quadratus lumborum block does offer analgesic and opioid consumption benefit S pinal morphine is considered to be the standard of care for postoperative analgesia after elective cesarean delivery performed under spinal anesthesia, 1 providing effective, safe, and cost-efficient analgesia up to 12 h postoperatively. 2 With the advent and recent proliferation of abdominal wall fascial plane blocks, including the relatively novel quadratus lumborum block, 3,4 investigators have reported that its use can improve postoperative pain relief when combined with 5,6 or used in place of spinal morphine, 7,8 after spinal anesthesia for cesarean delivery. The deposition of local anesthetic adjacent to the quadratus lumborum muscle not only treats the somatic pain associated with a Pfannenstiel incision but also spreads proximally to the paravertebral space 9,10 and may be advantageous in providing relief to the visceral component of postcesarean pain.…”
Section: What This Article Tells Us That Is Newmentioning
confidence: 99%
See 2 more Smart Citations